The open-holed trapdoor spiders (Mygalomorphae: Anamidae: Namea) of Australia’s D’Aguilar Range: revealing an unexpected subtropical hotspot of rainforest diversity - Rix, Michael G.; Wilson, Jeremy D.; Harvey, Mark S. (Zootaxa, 2020)
The D’Aguilar Range of subtropical south-eastern Queensland (Australia), harbours an upland rainforest biota characterised by high levels of endemic diversity. Following recent phylogenetic and biogeographic research into the open-holed trapdoor spiders of the genus Namea Raven, 1984 (family Anamidae), remarkable levels of sympatry for a single genus of mygalomorph spiders were recorded from the D’Aguilar Range. It is now known that eight different species in the genus can be found in the D’Aguilar uplands, with five apparently endemic to rainforest habitats. In this paper we present a phylogenetic and taxonomic synopsis of the remarkable anamid fauna of the D’Aguilar Range: a key to the eight species is provided, and four new species of Namea are described (N. gloriosa sp. nov., N. gowardae sp. nov., N. nebo sp. nov. and N. nigritarsus sp. nov.). In shining a spotlight on the mygalomorph spiders of this region, we highlight the D’Aguilar Range as a hotspot of subtropical rainforest diversity, and an area of considerable conservation value.